The Convergence of Manufacturing and Service Technologies: A Patent Analysis Approach - Geum, Youngjung; ., Yongtae Park; ., Sungjoo Lee (Information Management and Business Review, 2013)
Active technological convergence of manufacturing industries and service industries has been emerged as a core and essential phenomenon for recent business environment. Technology convergence has already been the basic force behind the both product innovation and service innovation, changing the ways in which firms interact with their customers. Despite the gravity, there has been limited approach to investigate the technological convergence of manufacturing technologies and service technologies from the empirical perspective. In response, this paper aims to investigate technological convergence between manufacturing technology and service technology using patent analysis. For this purpose, we define the service technology and manufacturing technology. Following on this, we analyze the USPC classification of those technologies to analyze the technological convergence. To investigate the dynamic change of convergence, 10-year-dyanamics are observed. As case studies, three industries which show high level of technological convergence of manufacturing and service - banking, healthcare, and education industries are selected and analyzed in detail.